Electro-Thermo-Mechanical Modeling of V-beam Actuators. (2015) - Chiorean, Radu-Stefan
Abstract: The purpose of this paper is to determine and validate the influence of the geometrical parameters of the V-beam thermal actuator on the output deflection and force. In order to achieve this goal, a parametric model was developed and validated both numerically and experimentally, a model that takes into account the geometrical parameters of the V-beam thermal actuator and a given actuation temperature. Furthermore, a calculus methodology for the temperature of the structure that also takes into account its geometrical parameters and a given actuation current was developed and validated both numerically and experimentally. By putting all this information head-to-head, the influence of the geometrical parameters of the V-beam thermal actuator on the output force and deflection is determined. This information can facilitate future design of task oriented V-beam type structures.